Modification of peroxidase activity and proteome in maize exposed to cadmium in the presence of galactoglucomannan oligosaccharides - Diana Hačkuličová; Eva Labancová; Zuzana Vivodová; Maksym Danchenko; Kristína Holeková; Marko Bajus; Danica Kučerová; Peter Baráth; Karin Kollárová (Ecotoxicology and Environmental Safety)
We tested the effects of galactoglucomannan oligosaccharides (GGMOs) and/or cadmium (Cd) on peroxidase activity and the proteome in maize (Zea mays L.) roots and leaves. Our previous work confirmed that GGMOs ameliorate the symptoms of Cd stress in seedlings. Here, the plants were hydroponically cultivated for 7 days, and the protein content and peroxidase activity were estimated in intracellular, neutral cell wall, and acidic cell wall protein fractions. The peroxidase activity varied between the plant organs as well as among the fractions and treatments. The GGMOs in the presence of Cd did not significantly influence content of peroxidases but modulated their activity, which implies posttranslational regulation. The changes in the content of various proteins (e.g., related to the defence reactions, cell wall structure/metabolism, and activation of plant hormones) caused by GGMOs and Cd indicate possible protective mechanisms that improve the vitality of maize seedlings exposed to metal stress. GGMOs partially reverted Cd-induced protein disbalance, which was a reoccurring phenomenon of mitigation in leaves.